Implementasi Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas XI IIS 1 SMAN 2 Baubau Sulawesi Tenggara - Sofyadin, Rifo Try (LaGeografia, 2019)
Is it true that the Based Learning Models to Improve Learning Outcomes of XI IIS 1 Class 2 State High School  Students’Baubau Southeast Sulawesi. This study is a classroom action research aimed at improving student learning outcomes and techer learning activities. The subject of this study were students of  XI IIS 1 Class 2 State High School  Baubau amounting to 36 people. Data collection uses test and observation methods that are filled by observers during the learning process. The data analysis tecnique used is descriptive analysis. Based on the results of the research obtained showed the learning outcomes of students in the first cycle of 73,52 experienced an increase in the second cycleof 86,61,while teacher activities with a persentage of 92,18 percent in cycle I and 97,65 percent in cycle II,the aplication of the problem based learning model can improve learning outcomes and the activities of geography teacher class XII IIS 1 class 2  state high school Baubau